Global Crisis: War, Climate Change and Catastrophe in the Seventeenth Century - Parker, Geoffrey (Yale University Press, 2013)
Revolutions, droughts, famines, invasions, wars, regicides, government collapses-the calamities of the mid-seventeenth century were unprecedented in both frequency and extent. The effects of what historians call the "General Crisis" extended from England to Japan, from the Russian Empire to sub-Saharan Africa. The Americas, too, did not escape the turbulence of the time. In this meticulously researched volume, master historian Geoffrey Parker presents the firsthand testimony of men and women who saw and suffered from the sequence of political, economic, and social crises between 1618 to the late 1680s. Parker also deploys the scientific evidence of climate change during this period. His discoveries revise entirely our understanding of the General Crisis: changes in prevailing weather patterns, especially longer winters and cooler and wetter summers, disrupted growing seasons and destroyed harvests. This in turn brought hunger, malnutrition, and disease; and as material conditions worsened, wars, rebellions, and revolutions rocked the world. Parker's demonstration of the link between climate change, war, and catastrophe 350 years ago stands as an extraordinary historical achievement. And the implications of his study are equally important: are we adequately prepared-or even preparing-for the catastrophes that climate change brings?